Penerapan Zakat pada Perusahaan Sawit di Provinsi Aceh - Muhammad Abthahi; Mulia Sari, Devi; Ardian (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
Qanun No. 3/2021 article 102, Paragraph 1 states that every company in Aceh is obliged to pay Zakat of 2.5 percent of the company's net profit through Baitul Mal. It is hoped that collecting corporate zakat can increase awareness of corporate zakat obligations as one of the pillars of economic and social development. It is hoped that palm oil companies, which are also an economic component, will also play a role in this matter, especially palm oil company zakat. The ineffectiveness of corporate zakat collection can be seen in the small number of companies that pay zakat every year. This research uses a literature study method. The results of this research can help palm oil companies in determining the amount of zakat from palm oil company net profits. The palm oil company sampled in this research is one of the palm oil companies in Aceh. The zakat potential for palm oil companies that is simulated to be calculated is only for two years, namely 2018 and 2019 according to their financial reports. This palm oil company is expected to be able to pay its palm oil company zakat in the coming year through Baitul Mal. The Company's Zakat that will be paid must have financial reports so that its financial performance can be measured.